2006
DOI: 10.1021/nl0622000
|View full text |Cite
|
Sign up to set email alerts
|

Excitons and Peierls Distortion in Conjugated Carbon Nanotubes

Abstract: We investigate coupled excitonic and vibrational effects in carbon nanotubes using a time-dependent Hartree-Fock approach. The results reveal intricate details of excited-state dynamics. In the ground state, spontaneous uneven distribution of the pi electrons over the bonds (i.e., Peierls dimerization) is observed throughout the entire nanotube, particularly in large-radius CNTs. However, we demonstrate that vibrational relaxation following photoexcitations leads to substantial local distortion of the tube sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
77
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 44 publications
(137 reference statements)
9
77
0
Order By: Relevance
“…The amplitudes vanish at the tube edges, which reflects excitonic scattering (reflection) at the ends (39). Such exciton delocalization patterns are identical to those observed in other quasi-1D materials (23,24,38,40). Another important characteristic of the electronic excitation is the exciton coherence size L C (maximal distance between electron and hole along the tube axis).…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…The amplitudes vanish at the tube edges, which reflects excitonic scattering (reflection) at the ends (39). Such exciton delocalization patterns are identical to those observed in other quasi-1D materials (23,24,38,40). Another important characteristic of the electronic excitation is the exciton coherence size L C (maximal distance between electron and hole along the tube axis).…”
Section: Resultssupporting
confidence: 70%
“…All molecular systems are oriented along the z-direction, have a finite length of 9-12 nm, and comprise several repeat units. The nanotube lengths were chosen to be significantly larger than the diameter of the tube with characteristic exciton sizes [Յ 5 nm (23,24)]. For these conditions, the finite size of 1D systems is expected to reproduce well the properties in the infinite-size limit (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these phenomena are typical features of quasi-one-dimensional materials 20 such as conjugated organic 21 and organometallic 22 polymers, and mix-valence chains 23 . In particular, recent studies reveal many common electronic features observed in spectra of CNTs and conjugated polymers 7,9,13,24,25 . Figure 1 schematically shows the essential electronic states contributing to photophysics of these materials providing common comparison baseline.…”
mentioning
confidence: 99%